The Challenge Program on Water and Food: opportunities for adding value to experiences of using research for development (R4D) - Hall, Andrew (CGIAR Challenge Program on Water and Food, 2013)
The Challenge Program on Water and Food (CPWF) is approaching the end of a second five-year phase. A distinctive feature of the second phase of CPWF is its explicit use of a Research – for – Development (R4D) approach. The focus of this report is to explore the value of the lessons that this R4D experience holds for others and to suggest ways in which this experience could be leveraged in debates and practice beyond CPWF.